Answer:
1) 3x³ - x² - 15x + 5
2) x² - 4
3) (5, 3)
4) f⁻¹(x) = 1/3x - 4
Explanation:
1......................
Given
- f(x) = 3x - 1
- g(x) = x² - 5
- f(x) · g(x) =?
Solution
- f(x) · g(x) = (3x - 1)(x² - 5) =
- 3x·x² - 3x·5 - x² + 5 =
- 3x³ - x² - 15x + 5
Correct option is A.
2......................
Given
- f(x) = x²
- g(x) = x - 4
- g(f(x)) =?
Solution
Correct option is D.
3......................
Point (5, 3) is the inverse of point (3,5)
Correct option is C
4......................
Given
Solution
To get the inverse of the function, switch over domain and range:
- x = 3f⁻¹(x) - 12
- 3f⁻¹(x) = x - 12
- f⁻¹(x) = 1/3x - 4
Correct option is D.